Neonatal Mortality and Neonatal Health Services in Wad Madani Pediatric Teaching Hospital - Elrofay, Mey M.; Eljak, Imad Eldin; Miskeen, Elhadi I. (Gezira Journal of Health Sciences; Vol 2 No 1 (2006), 2006)
The main objectives of this study are to describe the neonatal health and neonatal health services in Wad Madani Teaching Hospital also to identify the problems which cause death. Methodology: This is a descriptive retrospective study carried   out in Wad Madani Pediatric Teaching Hospital, in a period from January to October 2003. Data was collected from hospital records; observation and interview. Results: the majority of deaths were due to prematurity 33.3%, neonatal sepsis 24.3% and birth asphyxia 20%.  The neonatal mortality (NM) to total neonatal admission from January to October 2003 was 14.6% and 41.9% of total hospital deaths. Conclusion: Our conclusions ; Neonatal death in Wad Madani Teaching Hospital was found to be significantly high , strengthening of referral system recommended and special equipments that are not available in the Wad Madani Pediatric Teaching Hospital should be provided.